Implants for surgery - Hydroxyapatite - Part 4: Determination of coating adhesion strength (ISO 13779-4:2002, IDT) - Abdul Razak, Noor Hayati; Yaakop, Salbiah; Choon, David; Raj, Caroline; T, Mahadevan; Wong, Darren; Law, Ching Yee; How, Kim Chuan; Singh, Harwant; Yusof, Shahril; Manickam, Thirumal; Mohd Yusof, Hyzan; et al. (SIRIM, 2010)
This Malaysian Standard specifies test methods for measurement of the adhesion strength of hydroxyapatite coatings intended for use on components of surgical implants.